Effects of ergonomics practices on home workstation towards employee's physical health conditions / Krystle Jameela Mathew San - Krystle Jameela, Mathew San (2021)
This study was conducted to observe the ergonomics practice on home workstation of employees who are working from home. A survey on ergonomics practices on home computer workstation was sent to the respondents through social media platform and email. The respondents involved white-collar professional employees in Malaysia, aged from 20 and above, who transitioned from office to home due to the COVID-19 pandemic. The survey includes questions relating to demographic profile of the respondents, computer workstation ergonomics self-assessment checklist, and standardized questionnaires for analysis of the musculoskeletal symptoms on the wellbeing resulting from the workstation conditions. It was found that the homeworking employees experienced many physical discomforts in body regions specifically in the neck (n=147, 69.7%), shoulder (n=148, 70.1%), upper back (n=139, 65.9%) and lower back (n=135,64%). Pearson correlation analyses were performed to examine the relationship between primary outcomes of musculoskeletal discomforts due to workstation conditions and the sitting postures which resulting in negative correlations. It was found that majority of the homeworking employees suffered poor body postures due to poor workstation and work practice at home